Development Of Community Psychiatric Crisis Management Indicators And Assessment Framework In Taiwan: A Focus Group Study - Shu-Fang Su; Jiin-Ru Rong; Jin-Biau Li (European Scientific Journal, ESJ, 2016)
This study was to develop the Community Psychiatric Crisis Management (CPCM) Model for community-dwelling psychiatric patients of Taiwan. Purposes of this study were: 1. To develop psychiatric patients’ community crisis management indictors; 2. To develop the psychiatric patients’ community crisis management framework. Methods: Three focus group interviews involving a total of 42 experts, included psychiatrists, psychiatric nurses, social worker, and community mental health service providers were implemented. Interview data were analyzed with qualitative content analysis. Results: The model of CPCM concretized the objectives, crisis assessment indicators, and crisis intervention services for community psychiatric patients, and proved to be an important part of CPCM. The level of crisis severity and impact of patient can be assessed by the four indicators: medical care seeking behaviors, psychiatric symptom severity and impact, history of violence and substance abuse, and protective factors of family and social support system. In addition, the severity and impact of CPCM score could be implement to provide home visiting care and crisis management interventions. The recommended CPCM model enabled community mental health care professionals’ assessment and management the patient’s crisis problems in three stages, from crisis, acute and maintenance stage. Conclusions: The CPCM model was improved practically, and the contents of the intervention were constructed. It is important to integrate crisis management with the preventive intervention to the community psychiatric patient care.